The effect of recombinant human lactoferrin from the milk of transgenic cows on Salmonella enterica serovar typhimurium infection in mice. Issue 1 (15th October 2015) - Wu, Jinghuan; Hu, Yujie; Du, Chunming; Piao, Jianhua; Yang, Lichen; Yang, Xiaoguang
Abstract : Recombinant human lactoferrin from the milk of transgenic cows has an antibacterial effect of alleviating infection against Salmonella enterica serovar typhimurium in BALB/c mice. Abstract : Lactoferrin (LF) is a multifunctional protein with antibacterial and immunomodulatory activities. Given this beneficial effect, transgenic approaches have been used to produce lactoferrin. The aim of the current study was to investigate the in vivo effect of recombinant human lactoferrin (rhLF) from the milk of transgenic cows on Salmonella enterica serovar typhimurium (ST) infection in mice. Two hours before the infection with 0.3 ml at 2 × 10 5 CFU ml −1 of ST, each animal in the ST + rhLF group received 0.3 ml of rhLF with 20 mg ml −1 concentration while the ST group received PBS as placebos with the same volume through oral gavage. The mice were infected with ST once only on the first day. After the infection, the mice received 0.3 ml of rhLF with 20 mg ml −1 (6 mg d −1 ) concentration or PBS, respectively, for 7 days. Mortality and weight were monitored daily. Bacterial enumeration in the blood, liver, and spleen and histopathological analysis of the liver, spleen, kidney and intestine were conducted. The results showed that rhLF decreased the bacterial load in the liver and spleen of mice, reduced the degree of mice hepatomegaly and splenomegaly, and attenuated infectious inflammation with less histopathological abnormalities in the liver, spleen and kidney of mice in the ST infection. This study showed that rhLF with 6 mg per day had antibacterial activity of alleviating the infection caused by ST bacteria, which indicated that rhLF could be used as a supplement in special products.